Home Lighting Control Based on Time Scheduling using Crontab - Suchendra, Devie Ryana; Putri Suryani, Dewi; Ikhsan Sani, Muhammad (School of Applied Science, Telkom University, 2018)
Access control system in smart home concept is a support system that affects especially on controlling the electronic devices. Along with advances in technology, the conventional access control system was developed into an electronic-based access control system. A conventional access control system such as manual electric switches is now beginning to be developed with an electric switch that can be controlled wirelessly from the web. Raspberry pi 2 model B is one of the minicomputers which can be used in an automatic access control system. By using GPIO (General Purpose Input Output) on Raspberry Pi, can be created by a wireless access control system, safe and effective. The purpose of this study is designing a prototype relay control system wirelessly model that can be accessed through the web, the result indicates the possibility of relay control to be remote. Crontab scheduling functions on the controller's relay are used, then the device can function based on a predetermined schedule, it is very helpful to turn on and off electrical devices home remotely. The form of a username and password authentication will be used to protect the system from being accessed by anyone. In the final phase of research, the system is evaluated at day and night using Crontab function. Meanwhile, the response time of the relay is within 1-2 seconds range.